Do target CEOs trade premiums for personal benefits? - Qiu, Buhui; Trapkov, Svetoslav; Yakoub, Fadi (Journal of Banking & Finance, 2014)
Using a sample of 2198 completed M&A transactions between 1994 and 2010 in which both target and acquirer are public US firms supplemented with hand-collected data for target CEO retention, we uncover a significantly negative relation between target CEO retention and takeover premiums received by target shareholders. Further, when the target CEO was not retained, we document a significantly negative relation between the relative importance of the severance pay received by the target CEO and takeover premium. Taken together, our findings, which hold in various robustness tests, suggest that target CEOs bargain shareholder value for personal benefits during corporate takeovers. Our findings have important policy implications for takeover disclosures.